PENGARUH WORKING CAPITAL MANAGEMENT TERHADAP PROFITABILITAS DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI DAN LEVERAGE, CURRENT RATIO SERTA SALES GROWTH SEBAGAI VARIABEL KONTROL (Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Ayuningtyas, Gearin Sekar; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2021)
ABSTRACT This study aimed to examine effect of working capital management (WCM) and profitability moderated by firm size of listed manufacturing firms in Indonesia. Profitability was measured by return on asset (ROA). The independent variable used in this study was the cash conversion cycle (CCC) which represented working capital management. Control variables consisted of leverage (LEV), current ratio (CR), and sales growth (SG). The sample used in this study was manufacturing company listed on the IDX (Indonesia Stock Exchange) during the period 2015-2019. The number of samples were 93 companies taken by purposive sample method. Analytical method of the study was panel data regression with Moderate Regression Analysis (MRA) which previously passed the classic assumption test. Fixed effect was chosen as the best model. The results showed that the cash conversion cycle (CCC) had a significant positive effect on ROA. Firm size (FS) had a significant positive effect on ROA. The leverage control variable (LEV) had a significant negative effect. Meanwhile, the current ratio (CR) and sales growth (SG) had an insignificant effect. The moderated regression results reveal that the relationship between cash conversion cycle and profitability was moderated by firm size.